THE ASSESSMENT OF SAFETY SYSTEMS IN WWER-1000 NUCLEAR REACTOR USING IAEA SIMULATOR - Trần Đăng Khoa; Trịnh Thị Tú Anh (Tạp chí Khoa học Đại học Đà Lạt)
In this study, the operation and response capability of safety system in nuclear reactor WWER-1000 was analyzed during the accidents that involved the failure of main circulation pump or feed water pumps. The nuclear reactor WWER-1000 simulator developed by IAEA showed that safety systems such as the EP, the PP and the AUU are capable of controlling the reactor power by adjusting the control rods during the accidents. Also, the ACP allowed the nuclear reactor to operate safely at 65%, 61 % and 39% power for the wheel jam of MCP-1, the trip of MCP-1 and the FWP-1 accident, respectively. Additionally, the water in steam generator remained at the original value (224 mm) by SG water level controller to ensure the heat exchange within the reactor.